Sustainable Natural Hazard Management in Alpine Environments - Veulliet, Eric.; Johann, Stt̲ter.; Weck-Hannemann, Hannelore. (Springer Berlin Heidelberg, 2009)
In the recent past a marked increase of the damages caused by natural hazard processes has been documented, for example by the Munich Re-Insurance. On a regional scale, a similar development can be observed in mountain regions such as the Alps, where it is particularly a rise in flood events that has caused the maximum amount of economic damage. Three major aspects may help to explain this phenomenon: The changing frequency-magnitude relationship of the natural hazard processes, the multiplication of the damage potential due to the socio-economic change, and the non-adequate way of coping with the changing risk by the official authorities. As a consequence, this book tries to address key questions related to these developments and to give answers to these problems. Question 1: How can the strategies for coping with the rise in extreme flooding be improved? Question 2: How can the damage potential and other socio-economic aspects be quantified? Question 3: How can new computer based technologies contribute to minimizing the risks related to alpine natural hazards? An initial chapter gives an overview of the global change aspects of natural hazards and their related risks. While three chapters outline answers to question 1, four chapters discuss question 2. Five chapters give examples of new technologies.